Glutathione antioxidant pathway activity and reserve determine toxicity and specificity of the biliary toxin biliatresone in zebrafish. Issue 3 (11th June 2016) - Zhao, Xiao; Lorent, Kristin; Wilkins, Benjamin J.; Marchione, Dylan M.; Gillespie, Kevin; Waisbourd‐Zinman, Orith; So, Juhoon; Koo, Kyung Ah; Shin, Donghun; Porter, John R.; Wells, Rebecca G.; Blair, Ian; et al.
Abstract : Biliatresone is an electrophilic isoflavone isolated from Dysphania species plants that has been causatively linked to naturally occurring outbreaks of a biliary atresia (BA)‐like disease in livestock. Biliatresone has selective toxicity for extrahepatic cholangiocytes (EHCs) in zebrafish larvae. To better understand its mechanism of toxicity, we performed transcriptional profiling of liver cells isolated from zebrafish larvae at the earliest stage of biliatresone‐mediated biliary injury, with subsequent comparison of biliary and hepatocyte gene expression profiles. Transcripts encoded by genes involved in redox stress response, particularly those involved in glutathione (GSH) metabolism, were among the most prominently up‐regulated in both cholangiocytes and hepatocytes of biliatresone‐treated larvae. Consistent with these findings, hepatic GSH was depleted at the onset of biliary injury, and in situ mapping of the hepatic GSH redox potential using a redox‐sensitive green fluorescent protein biosensor showed that it was significantly more oxidized in EHCs both before and after treatment with biliatresone. Pharmacological and genetic manipulation of GSH redox homeostasis confirmed the importance of GSH in modulating biliatresone‐induced injury given that GSH depletion sensitized both EHCs and the otherwise resistant intrahepatic cholangiocytes to the toxin, whereas replenishing GSH level by N‐ acetylcysteine administration or activation of nuclear factor erythroid 2‐like 2 (Nrf2), a transcriptional regulator of GSH synthesis, inhibited EHC injury. Conclusion : These findings strongly support redox stress as a critical contributing factor in biliatresone‐induced cholangiocyte injury, and suggest that variations in intrinsic stress responses underlie the susceptibility profile. Insufficient antioxidant capacity of EHCs may be critical to early pathogenesis of human BA. (Hepatology 2016;64:894‐907)